Structural and thermoelectric properties of hydrothermal-processed Ag-doped Fe2O3. Issue 13 (September 2018) - Park, K.; Hong, H.Y.; Jung, G.W.; Kim, D.H.; Hakeem, D.A.; Iqbal, A.
Abstract: Fe2- x Ag x O3 (0 ≤  x  ≤ 0.04) nanopowders with various Ag contents were synthesized at different hydrothermal reaction temperatures (150 °C and 180 °C). Their structural properties were fully investigated through an X-ray diffraction, a Fourier transform infrared spectroscopy, and an X-ray photoelectron spectroscopy. The hydrothermal reaction temperature, time, and Ag content remarkably affected the morphological characteristics and crystal structure of the synthesized powders. The Fe2- x Ag x O3 (0 ≤  x  ≤ 0.04) powders synthesized at 150 °C for 6 h and the Fe2- x Ag x O3 (0.02 ≤  x  ≤ 0.04) powders synthesized at 180 °C for 12 h formed the orthorhombic α-FeOOH phase with a rod-like morphology, whereas the Fe2- x Ag x O3 (0 ≤  x  ≤ 0.01) powders synthesized at 180 °C for 12 h formed the rhombohedral α-Fe2 O3 phase with a spherical-like morphology. The Fe1.98 Ag0.02 O3 fabricated by utilizing Fe1.98 Ag0.02 O3 powders synthesized at 180 °C showed the largest power factor (0.64 ×10 −5 Wm −1 K −2 ) and dimensionless figure-of-merit (0.0036) at 800 °C.